Twelve-Month Efficacy and Safety Data for the "Stress Incontinence Control, Efficacy and Safety Study": A Phase III, Multicenter, Prospective, Randomized, Controlled Study Treating Female Stress Urinary Incontinence Using the Vesair Intravesical Balloon. Issue 3 (May 2018) - Winkler, Harvey; Jacoby, Karny; Kalota, Susan; Snyder, Jeffrey; Cline, Kevin; Robertson, Kaiser; Kahan, Randall; Green, Lonny; McCammon, Kurt; Rovner, Eric; Rardin, Charles
Abstract : Objectives: The "Stress Incontinence Control, Efficacy and Safety Study" (SUCCESS) is a phase III study of the Vesair Balloon in women with stress urinary incontinence who had failed conservative therapy, and either failed surgery, were not candidates for surgery, or chose not to have surgery. The safety and efficacy of the balloon at 12 months is reported for those participants in the treatment arm who elected to continue with the SUCCESS trial beyond the primary end point at 3 months. Methods: The SUCCESS trial is a multicenter, prospective, single-blinded, randomized, sham-controlled study. Participants were randomized on a 2.33:1 basis to either Vesair Balloon placement or placebo. The primary efficacy end point was a composite of both a greater than 50% reduction from baseline on 1-hour provocative pad weight test and an at least 10-point improvement in symptoms on the Incontinence Quality of Life questionnaire assessed at the 3-month study visit. Patients in the treatment arm who opted to continue in the trial were followed up prospectively up to 12 months. Results: A total of 221 participants were randomized, including 157 in the treatment arm and 64 in the control arm. Sixty-seven participants in the treatment arm (42.7% of participants enrolled) were evaluated at 12 months, with 56.3% achieving the composite end point and 78.7% having greater than 50% reduction in pad weight from baseline in a per-protocol analysis. In an intent-to-treat analysis treating all participants who did not continue with the balloon as failures, 24% of the participants achieved the composite end point and 33.6% had a greater than 50% reduction in pad weight from baseline. Treatment-related adverse events in this group included dysuria (40.1%), gross hematuria (36.9%), and urinary tract infection (26.1%). Conclusions: In this phase III trial, symptom relief was maintained for those participants who continued therapy for 12 months. The balloon was found to be safe with no device- or procedure-related serious adverse events reported. Additional studies are warranted to determine which patient populations are more tolerant of the balloon and to assess the efficacy and safety of its longer-term use. Additional screening methods, including screening patients for balloon tolerability, are warranted to reduce participant withdrawals. Abstract : 12-month SUCCESS study data demonstrates the safety and efficacy of the Vesair Balloon for the treatment of SUI in those subjects that tolerate the intravesical device.